Ketamine as the anaesthetic for electroconvulsive therapy: the KANECT randomised controlled trial – CORRIGENDUM. (6th April 2018) - Fernie, Gordon; Currie, James; Perrin, Jennifer S.; Stewart, Caroline A.; Anderson, Virginica; Bennett, Daniel M.; Hay, Steven; Reid, Ian C.
Summary: This notice describes a correction to the above mentioned paper.